AKUNTABILITAS KINERJA PEMERINTAH DAERAH (STUDI PADA PEMERINTAH DAERAH KABUPATEN MANOKWARI ) - , JAMES AGUUS WORIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to find empirical evidences of performance based management influences consisting of clear and measured objectives, decentralization, performance measurement system, and incentive toward performance and accountability of Regency Government of Manokwari. This study used mixed method with explanatory sequential design. Two preliminary research phases were conducted by using quantitative methodâSEM (Structural Equation Model) method and PLS (Partial Least Square path modeling) variance approach. Obtaining the result then qualitative method was conducted by using thematic content analysis. The study results show that clear and measured objectives significantly and positively affect quantitative and qualitative performance, but they significantly do not affect accountability. Decentralization significantly and positively affects quantitative and qualitative performance, but it significantly does not affect accountability. Performance measurement system significantly and positively affects quantitative and qualitative performance and accountability. Incentive significantly and positively affects qualitative performance and accountability, but it does not significantly affect quantitative performance. Based on the results and discussion in this study, implementation and practices of performance based management in Regency Government of Manokwari are supposed to be influenced by Institutional Theory